A Hybrid Imaging Platform(CT/PET/FMI) for Evaluating Tumor Necrosis and Apoptosis in Real-Time - Kang, Yulin; Zhai, Xiaohui; Lu, Sifen; Vuletic, Ivan; Wang, Lin; Zhou, Kun; Peng, Zhiqiang; Ren, Qiushi; Xie, Zhaoheng (Frontiers in Oncology, 2022)
Multimodality imaging is a unique approach of monitoring tumor biological behavior and therapy in vivo. We have developed a novel hybrid tri-modality system that includes two molecular imaging methods: Positron Emission Computed Tomography (PET) and Fluorescence Molecular Imaging (FMI) and the anatomic imaging modality X-ray Computed Tomography (CT). The following paper describes the system development and the imaging performance of tumor detection and therapy in vivo by using a new recombinant bacterial gene delivery approach (IL-24 expressing strain) into Balb/c nude mice bearing a head and neck tumor xenograft. Briefly, tumor burden and bacteria-induced apoptosis were detected using indocyanine green fluorescence in vivo imaging and PET using a novel 18F-labeled 2-(5-fluoropentyl)-2-methyl malonic acid tracer. In addition, a CT was used to evaluate the anatomical situation of living mice. The imaging performance has been validated by both a phantom and in vivo. An increased growth inhibition, as well as an increased tumor cell apoptosis induction, was observed in the treatment group compared to the control groups using tri-modal system. Besides, our results suggest that a new bacteria strain is a promising therapeutic approach against tumor growth in vivo. By being able to offer concurrent morphological and functional information, our system is able to more accurately characterize malignant tissues. Therefore, our self-developed tri-modality system (PET/CT/FMI) has been demonstrated to be an effective imaging tool to investigate and monitor tumor progression and therapy success in vivo simultaneously.